Economic Performance in Regulated and Unregulated Environments: A Comparison of U.S. and Canadian Railroads - Caves, Douglas W.; Christensen, Laurits R.; Swanson, Joseph A. (Quarterly Journal of Economics, 1981)
An opportunity to compare economic performance under substantially different levels of regulation is afforded by the differences in the regulatory environments of U. S. and Canadian railroads. We find that the less regulated Canadian railroads have achieved far higher productivity growth than have U. S. railroads. Furthermore, in spite of natural conditions favoring U. S. railroads, Canadian railroads have achieved a higher level of productivity. These findings for the typical U. S. and Canadian railroad are borne out by similar results for specific railroads. Had U. S. railroad productivity grown at the Canadian rate, U. S. railroad costs would be several billion dollars less each year.